Factors affecting the development of liver fibrosis in patients who experienced COVID-19 - M. V. Kruchinina; N. E. Pershina; I. O. Svetlova; E. V. Kruchinina (Бюллетень сибирской медицины, 2023)
The aim of the review is to highlight the main factors affecting the development of liver fibrosis and possible mechanisms of liver damage in patients who have experienced COVID-19. A search was carried out using keywords in the Scopus, Web of Science, and PubMed databases in literary sources of the last three years on factors associated with fibrogenesis in novel coronavirus infection.The review presents the main mechanisms of liver damage in COVID-19: direct effects on hepatocytes and cholangiocytes, hypoxia, and immune-mediated and drug-induced damage. We analyzed the significance of factors affecting fibrosis development in patients with COVID-19: chronic diffuse liver diseases, against which COVID-19 occurs, such as non-alcoholic fatty liver disease, alcohol-associated liver disease, chronic hepatitis B, C, and cirrhosis of the liver.Damage to the liver in coronavirus infection develops by several mechanisms. The development of COVID-19 against the background of diffuse liver pathology of various genesis is associated with progression of these diseases (increased fibrogenesis) and a poorer prognosis.